Viver o campo e a educação: experiências escolares de jovens em uma escola família agrícola - Cláudia Maria Teixeira Coelho (2009)
The research examined the school experience for young people who lives in rural areas in an Agricultural Family School in the city of Itaobim, Vale do Jequitinhonha/MG. The object of study is the condition of youth in the field and its relationship with the school in the context of the Alternation Pedagogy. The informants were selected according to the following criteria: gender, youth with greater or lesser adherence to school; time at school and availability to collaborate on the study. The research was qualitative and data collection was achieved by the realization of 15 semi-structured interviews with young people and school personnel, field observation, application of 108 questionnaires and document analysis. Authors of the Youth Sociology and the Education Sociology, in particular the studies on paths and youth school experiences, were employed as theoretical frameworks. The presented results indicate the diversity that is present in the youth of the field, which is reflected in multiple paths and school experiences and brings new challenges for the school organization, the pedagogic practices and the teacher-student relationship in the context of the Agricultural Family Schools.